Polyphenols as possible bioprotectors against cytotoxicity and DNA damage induced by ochratoxin A - Cariddi, Laura Noelia (2015)
The present study aimed to investigate the protective effects of luteolin (L), chlorogenic acid (ChlA) and caffeic acid (CafA) against cyto-genotoxic effects caused by OTA. Vero cells and rat lymphocytes were used and viability was measured by neutral red uptake, MTT and trypan blue dye exclusion method. L (50 and 100 µg/mL), ChlA (100 and 200 µg/mL) and CafA (10-50µg/mL) reduced the damage induced by OTA (10 µg/mL) on both cells type shown a good protective effect. The comet and micronucleus tests in Balb/c mice were performed. ChlA (10 mg/kg bw) reduced OTA (0.85 mg/kg bw)-induced DNA damage on blood and bone marrow cells, CafA (10 mg/kg bw) showed protective effect only in blood cells and luteolin (2.5 mg/kg bw) failed to protect DNA integrity on cells. In conclusion, polyphenols tested reduced the toxicity caused by OTA on different target cells with good protective effect, being ChlA the compound that showed the best effects.